Elements of Child Psychology in Alice Munro‘s ―Deep-Hole‖: An Overview - Malhotra, Dr. Nitin (International Journal of Psychosocial Rehabilitation, 2020)
Short stories amplify a wider impact on the psychology of the reader as they have been developed over time from their parent form novel. In classical texts, the genre has received prominence in the form of tales of oral literature, but in English Literary writings it has blossomed with the writings of Edgar Alan Poe, translations of the short stories of Guy De Maupassant, Anton Chekhov and many tales translated from the classical texts of Indian origin. Short-stories limn the imperative of the human life in a perspicuous way. In the same vein, Alice Munro has gained fame to her credit as a short story writer portraying the problems, tensions and conflicts of the human relationships and their consequences in the present era. She touches upon the psyche of the human mind with her art of writing short stories. Her short story “Deep-Holes” deals with the psychological aspect of a child reflecting the conflicts and frantic situations.Freudian concept of „id‟ procures the clear replica of Kent‟s state of mind. The finding indicates that the main character, Kent, passes the four most important of the developmental phases described by Erik Erikson as trust-versus-mistrust, autonomy-versus- shame-and-doubt, the initiative-versus guilt, industry-versus-inferiority. The events, dialogues and characters in the story overwhelm the reader to understand critically the aspirations, demands and familial misunderstandings happening in the present day.